Implementation of Government Policies in Pandemic Management Covid-19 in Indonesia - Hasriani Timung (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Introduction: Implementation of government policies in tackling the Covid 19 pandemic in Indonesia is an effort by the government to deal with cases of coronavirus disease (COVID-19). By understanding the efforts, steps, and policies formulated and implemented by the government, it can be assessed the handling strategy. Method: To analyze used deliberative policy analysis approach. This approach analyzes the narratives and arguments of the authorities to understand decision-making and policy implementation. This paper uses a qualitative approach by utilizing descriptive methods of analysis. Meanwhile, the data collection techniques used are literature studies that utilize government regulations, FMD, KMK, SE, journal articles, online news as well as the websites of authoritative institutions. The results of this analysis are: first, a positive and negative narrative to the government's response to prevent the transmission of COVID-19 because it has expanded various policies for covid-management and formed a task force and task force to combat COVID even though some policies are considered too late. Second, coordination between stakeholders, between the central government and local governments, between ministries and other state institutions already exist in the regulations of their respective ministries but have not been well-coordinated in their implementation so that it seems as if each moves on their own and some seem contradictory. Third, residents are still disobedient, indifferent to the government's call for discipline in implementing health protocols. This results in slower handling efforts because there is no awareness that pandemics can be controlled faster if the community actively provides support. Conclusion: This combination of three factors plays a major role in the government's efforts to control the spread of COVID-19 in Indonesia although it still needs improvement along with the pandemic in Indonesia.